Violence Against Women and Girls : Disaster Risk Management Brief - Gennari, Floriza; Arango, Diana; Urban, Anne-Marie; McCleary-Sills, Jennifer (World Bank, Washington, DC, 2015)
Violence against women and girls (VAWG) has negative impacts on physical and mental health. Health care settings provide a unique opportunity to identify VAWG survivors, provide critical support services, and prevent future harm. Ample studies have shown that natural disasters, including tsunamis, hurricanes, earthquakes, and floods, disproportionately affect women and girls, who are at greater risk of violence and exploitation than men and boys in the face of uprooted housing and traditional support structures, disrupted access to services, and both structural and social obstacles to accessing food, relief, supplies, and latrines. A study conducted four years after Hurricane Katrina occurred in the United States found that the rate of new cases of VAWG among displaced women also increased and did not return to the pre-hurricane baseline during the protracted phase of displacement.